The Effect of Project-Based Learning Integrated with the SAMR Model (Substitution, Augmentation, Modification, Redefinition) on Student Learning Outcomes - Jauza Zahira Adhiana; Zulfiani Zulfiani (International Journal of STEM Education for Sustainability, 2026)
To improve student engagement and learning results, the use of technology in biology education necessitates a suitable pedagogical strategy. Nonetheless, traditional teaching approaches still predominate in classrooms, with little use of technology. The purpose of this study was to examine how using Project-Based Learning (PjBL) in conjunction with the Substitution, Augmentation, Modification, and Redefinition (SAMR) model affected students' learning results regarding the respiratory system. This study employed a non-equivalent control group design and a quasi-experimental methodology. Purposive sampling was used to pick 68 11th graders from a South Tangerang public high school for the research sample. Pretests and posttests with multiple-choice items that had undergone validity and reliability testing were used to gather data. Normalized gain (N-Gain) computation, the Shapiro-Wilk normality test, Levene's homogeneity test, and the Mann-Whitney test were used to analyze the data. According to the findings, the experimental class's average posttest score was roughly 29 points higher than the control class's. The experimental class's N-Gain value was 84.50%, or (₂g² = 0.845) (high category). The Asymp. Sig. (2-tailed) value for the Mann-Whitney test was 0.000 (0.05). These findings showed that using PjBL in conjunction with the SAMR model significantly improved students' learning outcomes.